Avistamientos del delfín manchado, Stenella attenuata (Cetacea: Delphinidae) en Bahía Culebra, Costa Rica, 1999-2000 - Rodríguez Sáenz, Karina (2004)
Parallel to a zooplankton study (1999-2000) observations were made (from an inflatable boat), on the presence of dolphins along a transect (~8 km long) on the axis of Culebra Bay (24 km2), Gulf of Papagayo, Pacific coast of Costa Rica. Dolphins were found during 20 of the 31 boat surveys conducted. The only species of cetacean found in the bay was Stenella attenuata, the spotted dolphin. These sightings were more frequent during the rainy season, particularly during the month of May of both years. The presence of S. attenuata in Culebra Bay might be associated to the abundances of fish and mollusks (their presumed prey: for example, squids), as evidenced by fishery statistics available for this zone of the Pacific coast of Costa Rica.